Assessment of Nutrient Content of Kansas Grasslands Enrolled in the Conservation Reserve Program - Allen G. Schwartz; Brandon J. Fraser; J. W. L. Banks; Sandy K. Johnson; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this collaborative field study was to evaluate the quality of standing Conservation Reserve Program (CRP) forages throughout the year and compare samples collected from different regions across the state. Study Description: Monthly forage samples (n = 206) were collected from 19 counties in Kansas by Extension personnel. Regions were assigned east or west based on the sample's location. The samples were analyzed based on percent crude protein, acid detergent fiber, neutral detergent fiber, total digestible nutrients, calcium, phosphorus, potassium, and magnesium (dry matter basis) with precipitation being a random variable. Regions were analyzed based on the nutrient quality for each month. The Bottom Line: Understanding the nutrient quality of CRP lands that are released for haying or grazing is critical for making informed supplementation and feeding decisions with producers. These data will contribute and add to the existing body of research on the nutrient content of forages for grazing.
Keywords: forage; nutrient; quality